Zu den mit ሰ (sägäd) gebildeten Namen äthiopischer Kaiser sowie anderer hoher Würdenträger des Reiches - Kleiner, Michael (Aethiopica, 2004)
From Lǝbnä Dǝngǝl (1508–40) to Ǝgwalä Ṣǝyon / Gwalu (1801–18), most Solomonic monarchs in addition to their baptismal name also bore a regnal name (sǝmä mängǝśt) of the structure “noun + sägäd”. In Ethiopian Studies, sägäd of these names has traditionally been interpreted as an apocopated form of sägädä, ‘to prostrate oneself, to show submission’. In his 1988 edition of Die Geschichte des Lebna-Dengel, Claudius und Minās, however, Manfred Kropp challenged this view. Starting out by arguing that with names such as Bǝrhan Sägäd and Mäsiḥ Sägäd a traditionally understood sägäd would lead to inacceptable results, Kropp through a number of steps came to the conclusion that sägäd should best be seen as an adjective and be translated as ‘venerable’, an interpretation already once forwarded by Ludolf. The present article examines Kropp’s argument in detail, and concludes that it should be rejected. Conversely, it undertakes to demonstrate in a variety of ways, including the presentation of fresh evidence from Gǝʿǝz literature, that the traditional understanding of sägäd should – and can – be retained. In the process it also shows how this traditional understanding can be reconciled with names such as Bǝrhan Sägäd and, especially, Mäsiḥ Sägäd. In addition, the article proposes a new interpretation of the female regnal names formed with mogäsa in the position of male sägäd.